ANALISIS PEMANFAATAN QUEUE TREE PADA MIKROTIK DALAM MENGELOLA BANDWITDH JARINGAN HOTSPOT BERBASIS VOUCHER STUDI KASUS KOS 16A - Syah, Muhammad Fayza Ardian; Sutanto, Yudi (Unit Penelitian, Pengabdian Kepada Masyarakat dan Penjamnan Mutu Akademi Komunitas Negeri Pacitan, 2025)
A stable and evenly accessible internet network is crucial in boarding house environments with multiple users. However, problems often arise when some users access high-bandwidth services, such as downloading games or video streaming, causing the network to become slow or inaccessible. To address this issue, effective and structured bandwidth management is required to ensure fair bandwidth distribution for every user. This study aims to analyze the utilization of the Queue Tree feature on Mikrotik devices for managing bandwidth in a voucher-based hotspot network within a boarding house environment. By using this method, bandwidth distribution can be controlled to maintain internet access quality for each user, even during periods of intensive simultaneous usage. The analysis results show that using Queue Tree can enhance network stability and provide a more balanced bandwidth distribution, thereby improving the overall internet access quality in the boarding house. This study is expected to serve as a reference for network administrators in boarding house environments to implement effective bandwidth management strategies.